ANALISIS FIQH MUNAKAHAT TERHADAP PENUNDAAN PERNIKAHAN DI TENGAH WABAH CORONA VIRUS DISEASE 2019 DI KENTEN LAUT KECAMATAN TALANG KELAPA KABUPATEN BANYUASINN) - Rini Anggraini; Armasito Armasito (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
From the results of this study, it can be seen: The delay of marriage in the midst of the Covid-19 outbreak in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency was motivated by several things, namely a circular letter from the minister of religion, prospective husbands who were out of town, and wanted to hold a big reception. -magnitude. The postponement of marriage in the midst of the Covid-19 outbreak in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency, in Islamic law, the marriage law is Mubah. It is said to be permissible because to prevent the spread of the Covid-19 virus so that there is no process that can bring people together to hold a wedding reception, Islamic law teaches us to do better things than harm. The method used in this research is qualitative, while the type of research isfield research. While the data sources are divided into two, namely primary and secondary data. Furthermore, in data collection using interviews, literature and documentation and then analyzed usingmethods qualitative descriptive. Keywords: Marriage, Delay, Fiqh Munakahat